The Effect of Technical Competence and Certification Training on Employee Performance at PT. Petrokopindo Cipta Selaras - Ela Wahyu Diyanti; Ika Korika Swasti (Indonesian Journal of Business Analytics, 2023)
Competition in the business world makes every company must keep up with changes that occur, especially in the management of existing human resources. An important component of any business is its human resources. This research was conducted to find out (1) whether there is an effect of technical competency on performance, and (2) whether there is an effect of certification training on employee performance at PT Petrokopindo Cipta Selaras. The population and sample of this study amounted to 46 technicians. The research method used is quantitative, collecting data by distributing questionnaires directly to the respondents. The application of data analysis is Partial Least Square (PLS) with an ordinal measurement scale through a Likert scale. The result of this study is that technical competence does not affect employee performance, while the certification training affects the performance of employees at PT. Petrokopindo Cipta Selaras.